Ασθένειες του ξύλου: αμπέλια, πυρηνόκαρπα και μηλοειδή - Παναγιώτου, Δημήτρης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This work includes important data on the Cypriot vineyard as well as on the main local varieties. It is an overview of the major fungal diseases that cause the decomposition of wood in vineyards, stone and pome trees all over the world. In vines the main wood disease caused by eska, Eutypa dieback and Phomopsis dieback. In stone trees the main wood disease caused by Eutypa dieback and Leucostoma canker and in pome trees by Phaeoacremonium species and silver leaf diasease. Botryosphaeriae dieback is a common disease for all three crops. Also are mentioned, the main characteristic symptoms of these diseases in the trunk, leaves and other parts of the plant, the main causes of these diseases, various secondary metabolites and other substances involved in the process of infection of plants or in causing symptoms in plants. Also with regard to the treatment of wood diseases from the period of withdrawal arsenic sodium, are constantly spreading and causes great financial damages because there are no fungicides on the market that are facing them.
Keywords: Vines; Pome trees; Stone trees and wood diseases; Αμπέλια; Μηλοειδή; Πυρηνόκαρπα; Ασθένειες του ξύλου